Unraveling the microecological mechanisms of phosphate-solubilizing Pseudomonas asiatica JP233 through metagenomics: insights into the roles of rhizosphere microbiota and predatory bacteria - Tang, Yuhan; Wang, Linlin; Fu, Jing; Zhou, Fangyuan; Wei, Hailei; Wu, Xiaoqing; Fan, Susu; Zhang, Xinjian (Frontiers in Microbiology, 2025)
The effects of phosphate-solubilizing bacteria (PSB) on plant productivity are high variable under field conditions. Soil phosphorus (P) levels are proposed to impact PSB performance. Furthermore, the effect of exogenous PSB on rhizosphere microbial community and their functions are largely unexplored. Our study examined how different P background and fertilization affected the performance of PSB Pseudomonas asiatica JP233. We further conducted metagenomic sequencing to assess its impact on rhizosphere microbiota and functions, with a focus on genes related to soil P cycling. We found that JP233 could enhance P solubilization and tomato growth to different extent in both high and low P soils, irrespective of P fertilization. It was particularly effective in high P soil without extra fertilization. JP233 altered the rhizosphere microbial community, boosting taxa known for plant growth promotion. It also changed soil gene profiling, enriching pathways related to secondary metabolite biosynthesis, amino acids, carbon metabolism, and other key processes. Particularly, JP233 increased the abundance of most P cycle genes and strengthened their interconnections. Populations of certain predatory bacteria increased after JP233 inoculation. Our findings provide valuable insights into PSB’s mechanisms for P solubilization and plant growth promotion, as well as potential adverse impacts of resident microbes on bioinoculants.